2013
DOI: 10.1590/0001-37652013110812
|View full text |Cite
|
Sign up to set email alerts
|

Horse spleen segmentation technique as large animal model of preclinical trials

Abstract: The parenchymal distribution of the splenic artery was studied in order to obtain anatomical basis for partial splenectomy. Thirty two spleens were studied, 26 spleens of healthy horses weighing 320 to 450kg, aged 3 to 12 years and 6 spleens of fetus removed from slaughterhouse. The spleens were submitted to arteriography and scintigraphy in order to have their vascular pattern examined and compared to the external aspect of the organ aiming establish anatomo-surgical segments. All radiographs were photographe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 7 publications
0
7
1
Order By: Relevance
“…A partial splenectomy was performed in this case, which to the authors’ knowledge has not been previously reported in live equines (Foz Filho et al . 2013). The literature describes both minimally invasive and traditional surgical methods to access and remove the equine spleen.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A partial splenectomy was performed in this case, which to the authors’ knowledge has not been previously reported in live equines (Foz Filho et al . 2013). The literature describes both minimally invasive and traditional surgical methods to access and remove the equine spleen.…”
Section: Discussionmentioning
confidence: 99%
“…Two anatomo‐surgical segments dividing the spleen approximately in half were characterised (Foz Filho et al . 2013). However, the splenic lesions in this colt involved close to 70% of the organ's parenchyma.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A study of the angioarchitecture of the normal equine spleen as an anatomical basis for partial splenectomy has also been documented (Foz Filho et al . 2013). However, splenic abscesses are usually associated with extensive adhesions to the body wall and associated intra‐abdominal organs, including the intestinal tract.…”
mentioning
confidence: 99%